The Cell Wall-Derived Xyloglucan Is a New DAMP Triggering Plant Immunity in Vitis vinifera and Arabidopsis thaliana - Claverie, Justine; Balacey, Suzanne; Lemaître-Guillier, Christelle; Brulé, Daphnée; Chiltz, Annick; Granet, Lucie; Noirot, Elodie; Daire, Xavier; Darblade, Benoît; Héloir, Marie-Claire; Poinssot, Benoit (Frontiers in Plant Science, 2018)
Damage-associated molecular patterns (DAMPs) are endogenous molecules that can activate the plant innate immunity. DAMPs can derive from the plant cell wall, which is composed of a complex mixture of cellulose, hemicellulose and pectin polysaccharides. Fragments of pectin, called oligogalacturonides (OG), can be released after wounding or by pathogen-encoded cell wall degrading enzymes (CWDEs) such as polygalacturonases (PGs). OG are known to induce innate immune responses, including the activation of mitogen-activated protein kinases (MAPKs), production of H2O2, defense gene activation and callose deposition. Thus we hypothesized that xyloglucans (Xh), derived from the plant cell wall hemicellulose, could also act as an endogenous elicitor and trigger a signaling cascade similar to OG. Our results indicate that purified Xh elicit MAPK activation and immune gene expression in grapevine (Vitis vinifera) and Arabidopsis (Arabidopsis thaliana) to trigger induced resistance against necrotrophic (Botrytis cinerea) or biotrophic (Hyaloperonospora arabidopsidis) pathogens. Xh also induce resveratrol production in grapevine cell suspension and callose deposition in Arabidopsis which depends on the callose synthase PMR4. In addition, we characterized some signaling components of Xh-induced immunity using Arabidopsis mutants. Our data suggest that Xh-induced resistance against B. cinerea is dependent on the phytoalexin, salicylate, jasmonate and ethylene pathways.